Co2 mitigation service of Costa Rican secondary forests as an economic alternative for joint implementation initiatives - Ortiz, Rosalba; Ramírez, Octavio; Finegan, Bryan (2015)
This paper summarizes work in progress by the Silviculture and Natural Forests Management Project (PROSIBONA) CATIE-COSUDE' on quantification and valuation of carbon sink service in humid tropical forests. The study deals specifically with secondary forests and the possibility for this ecosystem to be an option for Costa Rican joint implementation initiatives. The results demonstrated the economic potential of secondary forests for its carbon sink service, . basically for carbon storage. According to our calculations, if all of Costa Rican secondary forests were included in joint implementation accounting at the current negotiated price of US$10 tC stored, they could generate an estimated US$77.3 million during a period of 20 years that the current "carbon parking" schemes are promoted. If international negotiations determines that Joint Implementation Initiatives should use current best knowledge on marginal costs of global warming, preliminary valuation results suggest, that carbon storage by Costa Rican secondary forests could generate US$127.4 millions product of one time discounted economic benefits and carbon sequestration reach a value of US$308 per hectare per year. According with this study, promoting the preservation of secondary forest ecosystem Costa Rica could mitigate current and avoid future CO2 emissions.